ANALISIS PANDANGAN SUNNI SYÎ’AH DALAM MEMAKNAI AHL AL-BAIT: STUDI KOMPARASI TAFSIR AL-THÂBARI DAN TAFSIR AL-MÎZÂN - Suhayati, Mimi; Maula, Ni'matul; Zahroh, Atssania; Febriani, Nur Alfiyah; Baiti, Nur (ojs.unsiq.ac.id, 2024)
An advice conveyed by the Prophet to his people is to glorify their descendants or ahl al-bayt among them; The Prophet's wife, Ali bin Abi Talib, Fatima, Hasan, and Husain. This paper discusses the Sunni and Shia arguments in interpreting Ahl al-bayt based on two interpretations, al-Tabari and al-Mizan. Three things are studied: their understanding of interpreting ahl al-bayt, the taking of interpretation studies, and the differences of each school of thought in measuring the truth of history. The method we use is library research by taking primary sources in the form of books being studied, and secondary sources in the form of books, journal articles, and others. This discussion also summarizes the research results that glorifying the descendants of the Prophet is a form of respect. This must continue to be practiced until now, one of which is following da'wah studies from the descendants of the Prophet, namely Habib, Syarif, and Sayid.